-1/3(m-4)=2

Simple and best practice solution for -1/3(m-4)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1/3(m-4)=2 equation:


m in (-oo:+oo)

(-1/3)*(m-4) = 2 // - 2

(-1/3)*(m-4)-2 = 0

-1/3*(m-4)-2 = 0

-1/3*(m-4)-2 = 0

-1/3*m-2/3 = 0

-1/3*m-2/3 = 0

-1/3*m-2/3 = 0 // + 2/3

-1/3*m = 2/3 // : -1/3

m = 2/3/(-1/3)

m = -2

m = -2

See similar equations:

| 5x^2-3x-3=2x^2 | | 9y+14x=180 | | 3(-3)/5^-2 | | 3x^2+12x+32=0 | | 7[6x+1]=427 | | 3+x=7x-45 | | 3p-3/6 | | 8x+61/9=-3 | | x^3-3x^2-6x-4=0 | | 3p-3/6x3p^2/p^2-2 | | (5(24/35))/6 | | 7x-22/9=-4 | | 180n-360=(180n-360)/n | | y=8+-5x | | 3k-2=4k-7 | | 2x-4/9=-2 | | 2/3x15 | | Y=-5x+14 | | 2e^5x-2=10 | | 4b-6-6b-3= | | 2x/7=-6 | | 7(-2X+8/6+5)-2=12 | | (5x)/6=(4)/7 | | 4x-10=-50 | | 4x*x+11=12 | | 4x+55/7=-3 | | 6x+10=-2+7x | | 13b=2(3b-12)+3 | | 4(2x+1)=3(3x-2) | | 2x*x-7=-7 | | z=7+y | | 3v^2-33v+84= |

Equations solver categories